2010
DOI: 10.4103/1742-6413.67112
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopic evaluation of cervix with persistent inflammatory Pap smear: A prospective analytical study

Abstract: Background:Inflammatory Pap smear is the most common report received by a gynecologist. The cervical screening algorithm for benign cellular changes on the Pap smear recommends treatment of infection if indicated and a repeat Pap smear in 4 to 6 months time. If the inflammatory changes still persist, subject the patient to colposcopy. However, in practice, this is not followed, especially in developing countries like ours where proper screening protocols are not available. Hence, a good number of patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 6 publications
4
22
1
Order By: Relevance
“…The incidence of CIN and invasive carcinoma in women with persistent inflammatory pap smears over just 2 weeks was found to be 20.6% and 0.7%, respectively, in a study by Dasari et al [16] Hence, by waiting for a longer period of time before repeating the pap smear may lead to a delay in diagnosis of CIN in a high percentage of cases.…”
Section: Discussionmentioning
confidence: 95%
“…The incidence of CIN and invasive carcinoma in women with persistent inflammatory pap smears over just 2 weeks was found to be 20.6% and 0.7%, respectively, in a study by Dasari et al [16] Hence, by waiting for a longer period of time before repeating the pap smear may lead to a delay in diagnosis of CIN in a high percentage of cases.…”
Section: Discussionmentioning
confidence: 95%
“…We included repeated cervicitis as a colposcopy indication because in a recent study, a 16.67% incidence of CIN in women with persistent inflammatory pap smear was reported (Bhutia et al, 2011). The incidences of CIN and invasive carcinoma in women with persistent inflammatory pap smears over just 2 weeks were found to be 20.6% and 0.7%, respectively, in another study (Dasari et al, 2010). One must not see a report of inflammation on pap smear in isolation and ignore it as being insignificant.…”
Section: Reliability Of Colposcopy In Turkey: Correlation With Pap Smmentioning
confidence: 99%
“…Patients already diagnosed as cases of cervical cancer or treated for it were excluded from the study. The sample size was calculated using power analysis and sample size software based on different techniques as described in studies, the sample size was calculated to be n=145 10,11,12,13,14,15 Findings were noted on a proforma (colposcopy findings, cytology and histopathology reports). Abnormal cytology included ASCUS, LSILS, HSILS and invasive carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…23 A prospective study of India of 2008 shows that there is a lack of agreement between cytology and histopathology and it concludes that in patients who have persistent inflammatory pap smear can have cervical intraepithelial neoplasia 11 , according to a study there was agreement between pap smear and cervical biopsy ( k=0.5 ) 12 and another study concluded that a high agreement between cytology and histopathology exists of 82%…”
mentioning
confidence: 99%